EIB Working Papers 2020/03 - Employer provided training in Europe Determinants and obstacles (Volume 2020/3) - Brunello, Giorgio (European Investment Bank, 2020)
This report looks at employer-provided training in Europe. Starting with a brief outline of the economic theory of training, it turns to recent developments by combining data from two employer surveys, the European Investment Bank's Investment Survey (EIBIS) and Eurostat's Continuous Vocational Training Survey (CVTS). It reviews the recent empirical literature on the relationship between economic institutions and training and between training and productivity and considers whether financing constraints hamper the provision of training by firms. The paper concludes by discussing policy implications.